Impacto del uso de herramientas digitales en el aprendizaje y desarrollo de habilidades en niños y adolescentes de zonas rurales, Periodo Académico octubre 2024 - marzo 2025 - Espin Urrea, Jaime Rolando (2025)
Currently, it is essential that the teaching-learning process incorporates tools that contribute to the development of technological skills in society and, above all, help fulfill academic activities in a more innovative way. The purpose of this research project is to evaluate the impact of digital tools on children from rural areas belonging to the GADs (Decentralized Autonomous Governments) in the province of Los Ríos, which have agreements with the Technical University of Babahoyo to strengthen knowledge and gradually reduce the social disparities between urban and rural areas. The type of research used was descriptive and non-experimental, applying surveys, interviews, and observation sheets aimed at beneficiaries, parents, teachers, and representatives of the digital center where the courses on digital tools (Canva, Genially, and Loom) for Educational Digital Renewal and Improvement were conducted. The data obtained were presented in tables and statistical graphs, showing that these tools were effectively integrated into academic activities, enabling students to develop technical and creative skills.